Trends in the Development of Students' Research Activities (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article emphasizes the importance of students' research activities as a factor in their professional development. The current state of organization of research work of students in higher educational institutions is analyzed using the example of the Republic of Uzbekistan and the city of Bukhara. The directions, forms and methods of developing students' research activities in modern conditions are determined.